Scientific and pedagogical research in the field of theory and practice of professionally-oriented physical culture in higher education institutions of the Ministry of Internal Affairs of Russia - Gordienko, T.P.; Uskov, S.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to provide scientific and theoretical justification for the use of sports-oriented technologies in the practice of professionally-oriented physical education for cadets at Russian Ministry of Internal Affairs universities. Methods and structure of the study. Analysis and summarisation of scientific and methodological literature; synthesis of practical experience through interviews with veterans of the Ministry of Internal Affairs operational work, leading coaches and athletes, as well as viewing video recordings of operational and competitive activities; pedagogical observations and testing. Results and conclusions. The author’s interpretation sets out the provisions of a sports-based approach to the physical training of future police officers as arguments for the necessity and relevance of scientific and pedagogical research on the development of the theory and practice of domestic professionally-oriented physical culture. Important aspects of the use of sports-oriented technologies in educational organisations are noted: integrated training, the formation of motivation for the growth of professional skills, the conversion of the components of sports training, individualisation and a personality-oriented approach.